FOLK SONG STYLE AND CULTURE, by Alan Lomax, with contributions by the Cantometrics staff and with the editorial assistance of Edwin E. Erickson, Washington, D.C., American Association for the Advancement of Science "Publication No. 88”, 1969. Pp. xx, 363, with 76 tables, 75 charts and graphs, 3 appendices, bibliography, list of sources, index. - Pantaleoni, Hewitt (International Library of African Music, 1970)
pages: 130-131
Keywords: African Music